The Role of Village Government in Increasing Community Participation in Village Development - Faradila Arrahma (Penerbit Hellow Pustaka, 2026)
Participatory village development is key to achieving equitable and sustainable community welfare. This study aims to identify the role of village government in increasing community participation in village development and analyze the factors influencing it. The research method used is normative legal research, often referred to as doctrinal research. Normative legal research is a type of legal research that examines norms or rules in applicable laws and regulations. The primary focus of this method is the analysis of positive legal norms, including their content, systematics, and principles. The results indicate that community participation is influenced by various factors, including education level, leadership quality of the village head, transparency in fund management, local cultural values, previous participatory experience, and available communication media. Village government plays a strategic role in creating an environment conducive to participation through inclusive village deliberations, transparency of public information, and strengthening community capacity. This research confirms that collaboration between village governments and communities is the primary foundation for the success of democratic, locally-focused village development.